Impact of absorptive capacity of an enterprise on its strategic flexibility: empirical results - Stelmaszczyk, Monika (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
The aim of this paper is to enrich consideration on the concept of absorptive capacity with its impact on the strategic flexibility of an enterprise. Strategic flexibility has been described in two dimensions: resource flexibility and coordination flexibility. The survey was conducted at Vive Textile Recycling using a sample of 78 managers. Structural equation modeling (SEM) using the maximum likelihood method was used to test the hypotheses. The added value of this research is that it demonstrates the direct impact of potential absorptive capacity on resource flexibility and coordination flexibility. In addition, the mediating role of relative absorptive capacity in the relationships between the potential absorptive capacity and two dimensions of the strategic flexibility of the examined enterprise.